Protection System Coordination On 20 kV Distribution Network In Makassar City - Firdaus Firdaus; Andi Imran; Riana T. Mangesa; Firman Setia Waruru (Program Studi Teknik Elektro Universitas Khairun, 2023)
This study is a quantitative study that aims to a) describe the coordination of protection systems under abnormal conditions in the distribution network and b) to determine the selectiveity of protection systems in isolating equipment in abnormal conditions of distribution networks. Data setting existing rele protection system obtained in PT. PLN (Persero) UP2D Makassar, the data is then processed, simulated, and analyzed using the ETAP 19.0.1 program. The series analyzed in this study is the distribution network PLN ULP Karebosi Paotere refiner with a channel length of 8,234 km, where sktm channel 0.844 km and SUTM 7,390 km, consisting of 33 distribution substations. Â The results showed that the flow of short circuit disruption on Hatta buses was: 3-Phase by 3,887 kA, Line-to-Ground by 3,550 kA, Line-to-Line by 3,357 kA, and Line-to-Line-to-Ground by 3,831 kA. To achieve reliability and coordination of protection system equipment resetting rele on recloser Sabutung Set OCR 250 kA, TMS-TD OCR 0.08 s, moment OCR 3x, Sect. Paotere bridge OCR 200 kA, TMS-TD OCR 0.07 s, moment OCR Block, Sect. Hatta OCR 180 kA, TMS-TD OCR 0.05 s, moment OCR Block.